2020
DOI: 10.11591/ijphs.v9i1.20404
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of premenstrual syndrome and quality of life among health science college student

Abstract: <p>Premenstrual syndrome (PMS) is a set of affective, behavioral and physical symptoms with appear in the luteal phase that could affect productivity and quality of life. PMS in adolescents could affect academic performance, such as a decreasing in concentration, failed the exam and absenteeism in the class. The objective was to evaluate the prevalence of PMS and determine its effect on quality of life among female health science students. This cross-sectional study was conducted between July-September 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…(35) In the present study, it was found that, negative highly significant correlations were found between the studied females' quality of life and their physiological, psychological and behavioral symptoms of the total level of PMS. This agrees with (Kustriyanti D and Rahayu H, 2020 ), (38) who reported that the quality of life among students has decreased in all domain, physical health, psychological, social relationships and environment as well as (K.BHUVANESWARI et al, 2019), (3) and (Karpagavalli G and Raj Rani 2020), (24) who reported that PMS was associated with a poorer quality of life across all domains , In addition, ((Delara M et al 2012), (21) affirmed the fact that adolescents with premenstrual disorders suffer from poor health-related quality of life. Moreover, (Al-Batanony MA and Al-Nohair SF, 2014), found an association of PMS with physical problems, vitality, mental health and body pain, indicating decreased quality of life.…”
Section: -Statistical Analysissupporting
confidence: 91%
“…(35) In the present study, it was found that, negative highly significant correlations were found between the studied females' quality of life and their physiological, psychological and behavioral symptoms of the total level of PMS. This agrees with (Kustriyanti D and Rahayu H, 2020 ), (38) who reported that the quality of life among students has decreased in all domain, physical health, psychological, social relationships and environment as well as (K.BHUVANESWARI et al, 2019), (3) and (Karpagavalli G and Raj Rani 2020), (24) who reported that PMS was associated with a poorer quality of life across all domains , In addition, ((Delara M et al 2012), (21) affirmed the fact that adolescents with premenstrual disorders suffer from poor health-related quality of life. Moreover, (Al-Batanony MA and Al-Nohair SF, 2014), found an association of PMS with physical problems, vitality, mental health and body pain, indicating decreased quality of life.…”
Section: -Statistical Analysissupporting
confidence: 91%
“…Women suffering from PMS frequently miss work or school, resulting in a lower quality of life. This is related to factors such as premenstrual pain and a stressful environment (19). However, the higher prevalence of PMS among university students enrolled in health-related courses, as well as its impact on their quality of life, point to the importance of implementing educational practices that inform women about the syndrome because once informed, women are more likely to seek treatment, reducing the incidence of the syndrome and its negative impact on quality of life (20).…”
Section: The Effects Of Pms On Women's Regular Livesmentioning
confidence: 99%
“…In a systematic review examining the frequency of PMS in Turkey, the prevalence has been reported as 52.2% [ 3 ]. PMS, being such a widespread health issue, can negatively impact women's quality of life [ 1 , 4 7 ], thus highlighting the importance of PMS treatment.…”
Section: Introductionmentioning
confidence: 99%